Cranial nerves : functional anatomy - Monkhouse, Stanley (Cambridge University Press, 2013)
This clincally oriented survey of cranial nerve anatomy and function gives the main anatomical features of each nerve, followed by clinical aspects and details of clinical testing. Simple line diagrams accompany the text.